'Cornwallism' and Arguments against Greenhouse Gas Emissions Reductions. (December 2020) - Björnberg, Karin Edvardsson; Röcklinsberg, Helena; Sandin, Per
Opposition against greenhouse gas emissions reductions is strong among some conservative Christian groups, especially in the United States. In this paper, we identify five scripture-based arguments against greenhouse gas mitigation put forward by a core group of Christian conservatives ('the Cornwallists'): the anti-paganism argument, the enrichment argument, the omnipotence argument, the lack of moral relevance argument and the cost-benefit argument . We evaluate to what extent the arguments express positions that can be characterised as climate science denialist and to what degree they are consistent with support for climate adaptation. Using Stefan Rahmstorf's (2004) taxonomy of climate science denial, we conclude that the Cornwallists could be labelled climate change deniers. However, their opposition is not only based on denial of climate science but often rests on premises that render the science irrelevant, a position we term 'relevance denialism'.